Credit Risk Modelling and Implementation of Credit Risk Models in China - Yu, Mengxiao (2007)
Credit risk, or the risk of counterparty default, is an important factor in the valuation and risk management of financial assets. It has become increasingly important to financial institutions. A variety of credit risk models have been developed to measure credit risk. They are J.P. Morgan's CreditMetrics; KMV's PortfolioManager based on Merton (1974) option pricing model; macroeconomic model CreditPortfolio View developed by McKinsey; CSFB's Credit Risk+ Model based on actuarial science framework; and Jarrow and Turnbull's reduced-form model.